First thermal fatigue studies of tungsten armor for DEMO and ITER at the OLMAT High Heat Flux facility - D. Alegre; D. Tafalla; A. De Castro; M. González; J.G. Manchón; F.L. Tabarés; T. Hernández; M. Wirtz; J.W. Coenen; Y. Mao; E. Oyarzábal (Nuclear Materials and Energy, 2024)
The armor for future nuclear fusion reactors is one of the main areas of research due to the harsh conditions it will undergo. Thermal fatigue is one of the most serious damage, as it will cause any material to fail even if the heat and particle loads during the reactor operation are always maintained low. In this work we have compared the actual tungsten armor for ITER tokamak with a new advanced tungsten material: tungsten reinforced by tungsten fibers (Wf/W). ITER-like W has shown small intergranular cracking at heat loads similar to the ones found in other similar devices: heat flux factor of FHF = 5.2 ± 1.6 MW/m2s0.5. But at much lower number of pulses: 641 versus 105. H embrittlement by the high-energy ions of OLMAT has been postulated as one of the main reason of this relatively prompt cracking appearance. Opposed to this, the type of Wf/W studied here, Porous Matrix (PM-Wf/W), has shown no damage at the same conditions and up to 950 pulses. These results show the capabilities of OLMAT for fatigue studies in conditions relevant to a future nuclear fusion reactor. New upgrades of OLMAT will partially solve the issues found in this first phase. Future work to continue with fatigue studies will be addressed.